2019
DOI: 10.1039/c9sm00179d
|View full text |Cite
|
Sign up to set email alerts
|

Self-healable poly(acrylic acid-co-maleic acid)/glycerol/boron nitride nanosheet composite hydrogels at low temperature with enhanced mechanical properties and water retention

Abstract: A self-healable poly(acrylic acid-co-maleic acid) hydrogel at low temperature with excellent mechanical properties and water retention was fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…As a result, even though there are numerous reported instances of self‐healable hydrogels, the hydrogels with both high strength and high self‐healability are rather unusual, which severely limit the applications of these hydrogels. Recently, a series of strategies, such as nanocomposite [ 4,22–27 ] and double‐network (DN) [ 8,28,29 ] approaches, have been developed to cope with the above‐mentioned dilemma. Especially, the DN hydrogels consisted of two asymmetric polymer networks, have demonstrated to be able to effectively reinforce the hydrogels and dissipate the energy during deformation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, even though there are numerous reported instances of self‐healable hydrogels, the hydrogels with both high strength and high self‐healability are rather unusual, which severely limit the applications of these hydrogels. Recently, a series of strategies, such as nanocomposite [ 4,22–27 ] and double‐network (DN) [ 8,28,29 ] approaches, have been developed to cope with the above‐mentioned dilemma. Especially, the DN hydrogels consisted of two asymmetric polymer networks, have demonstrated to be able to effectively reinforce the hydrogels and dissipate the energy during deformation.…”
Section: Introductionmentioning
confidence: 99%
“…With further increase in the f‐BNNS content to 0.3 wt%, the tensile strength of the hydrogel decreased to 0.069 MPa due to the agglomeration of f‐BNNS. [ 18 ] Simultaneously, the tensile strain of hydrogel with 0.2 wt% f‐BNNSs was as high as 1457%, which was 772% of the pristine one (Figure 5c). The toughness of hydrogel with 0.2 wt% f‐BNNSs was also increased from 0.04 to 0.82 MJ m −3 , increased by 1950% (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…[ 24 ] As a result, the P(MAH‐β‐CD‐ co ‐NIPAM)/f‐BNNS hydrogels possessed excellent strength and tensile strain, making it superior to the majority of the reported PNIPAM‐based hydrogels (Figure 5e). [ 2,16–20,32 ] Moreover, the tensile strain of the P(MAH‐β‐CD‐ co ‐NIPAM)/f‐BNNS hydrogel is much higher than those of most nanocomposite hydrogels, which indicated that f‐BNNSs are ideal nanofillers because of strong dynamic interactions between f‐BNNSs and PNIPAM matrix. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations